2000
DOI: 10.1021/jm000372i
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors. 18. 6-Substituted 4-Anilinoquinazolines and 4-Anilinopyrido[3,4-d]pyrimidines as Soluble, Irreversible Inhibitors of the Epidermal Growth Factor Receptor

Abstract: 4-Anilinoquinazoline- and 4-anilinopyrido[3,4-d]pyrimidine-6-acrylamides are potent pan-erbB tyrosine kinase inactivators, and one example (CI-1033) is in clinical trial. A series of analogues with a variety of Michael acceptor units at the 6-position were prepared to define the structural requirements for irreversible inhibition. A particular goal was to determine whether additional functions to increase solubility could be appended to the Michael acceptor. Substituted acrylamides were prepared by direct acyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 19 publications
1
57
0
1
Order By: Relevance
“…Our initial selection of pharmacokinetically optimized (more hydrophilic) side-chain IPQA derivatives and their in silico SAR modeling with the activated EGFR kinase was based on previous reports [29Y31], which demonstrated that derivatization from the 6-and 7-positions of the quinazoline moiety for the compounds proposed in the current application does not inhibit their irreversible binding and inhibition of EGFR kinase. Specifically, the highly potent and irreversible inhibition of EGFR kinase activity has previously been demonstrated for the 6-acrylamido-4-(3-bromo-anilino)-7-(3-morpholin-1-yl-propyl)quinazolin, 6-acrylamido-4-(3-bromo-anilino)-7-(2-morpholin-1-ylethoxy) quinazolin [30,31], and (E)-But-2-enedioic acid [4-(3-halogeno-anilino)-quinazolin-6-yl]-amide-(3-morpholin-4-yl-propyl)-amide [29]. Moreover, in molecular structures of Iressa (AstraZeneca) and Tarceva (OSI Pharmaceuticals), both the 6-and 7-positions of the quinazolin moiety are derivatized with side chains as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial selection of pharmacokinetically optimized (more hydrophilic) side-chain IPQA derivatives and their in silico SAR modeling with the activated EGFR kinase was based on previous reports [29Y31], which demonstrated that derivatization from the 6-and 7-positions of the quinazoline moiety for the compounds proposed in the current application does not inhibit their irreversible binding and inhibition of EGFR kinase. Specifically, the highly potent and irreversible inhibition of EGFR kinase activity has previously been demonstrated for the 6-acrylamido-4-(3-bromo-anilino)-7-(3-morpholin-1-yl-propyl)quinazolin, 6-acrylamido-4-(3-bromo-anilino)-7-(2-morpholin-1-ylethoxy) quinazolin [30,31], and (E)-But-2-enedioic acid [4-(3-halogeno-anilino)-quinazolin-6-yl]-amide-(3-morpholin-4-yl-propyl)-amide [29]. Moreover, in molecular structures of Iressa (AstraZeneca) and Tarceva (OSI Pharmaceuticals), both the 6-and 7-positions of the quinazolin moiety are derivatized with side chains as well.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs were administered either orally or intraperitoneally using doses employed in murine models of proliferative disease (25,30,(43)(44)(45)) (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…4). The reason for this large difference in the performances of the two drugs might lie in the different pharmacokinetics and distribution of the drugs in mice, which is most likely influenced by the chemical substituents on the common 4-anilinoquinazoline scaffold of the drugs (20,30) (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR is expressed or highly expressed in a variety of human tumors including non-small cell lung cancer (NSCLC), breast, head and neck, gastric, colorectal, esophageal, prostate, bladder, renal, pancreatic, and ovarian cancers [8]. Particularly, a large number of compounds have been synthesized and evaluated as EGFR inhibitors, with special attention being paid to compounds having a phenyl amino pyrimidine moiety in their structures [9][10][11][12][13]. Evidently Anilinoquinolines are well known EGFR inhibitors as demonstrated in various studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%